The Dynamics of Mass Communication - Joseph R. Dominick (New York(State): McGraw-Hill, 1994)
This comprehensive, colorful, and anecdotal introduction to mass media has been updated to include the latest facts, figures, and statistics. Also included is new information on media personalities, corporations, innovative programming, and any recent changes in the regulations governing the various media industries. The updated 1994 Edition of "The Dynamics of Mass Communication" continues to have in-depth coverage of international communications and a critical discussion of the latest trends in technology.
(NP(B/14836-(NP(B/14837s
+Photos
Keywords: industry -- structure -- history